INOVASI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN TATAP MUKA TERBATAS PANDEMI COVID-19 DI MTsN 3 TRENGGALEK - Romandoni, Ilham Yahya (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
It is certainly not easy for teachers to overcome various obstacles in teaching due to the COVID-19 pandemic. Innovation in education is essential to overcome the problems caused by the COVID-19 pandemic. Problems in applying the knowledge learned arise when teachers' enthusiasm for innovation decreases. Educational innovation is needed to facilitate student learning during the COVID-19 pandemic. This study explains how COVID-19 Limits Face-to-Face Learning Activities, Media Choices and its Impact. This research uses a descriptive qualitative approach with a case study. Data sources consist of primary and secondary data. The primary sources of information are Islamic Religious Education Teachers and Students. Secondary data sources are documents. Data collection methods include observation, in-depth interviews and documentation. Analyzing research materials includes summarizing, presenting and summarizing data. Data validity checks include extended participation, continuous observation, and triangulation. The results of this study show that learning is managed by starting the learning process with dhuha prayers in the mosque, followed by learning  in the classroom, then the students begin with prayer, attendance, and explanation of the material. PAI teachers provide material to students and end again with prayer. The class lasts about 30 minutes. Face-to-face teaching is limited to a few classes. The selection of learning media uses technology frequently. In the utilization of technology, E-Learning in Madrasah and WhatsApp groups, while PowerPoint is the general media. As a result, the students can fully understand the material taught by the Religious Education teacher, become more persistent and active in learning, and be encouraged to study Islamic Religious Education subjects.